2019
DOI: 10.1159/000496431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine Intake on Postoperative Ileus: A Systematic Review and Meta-Analysis

Abstract: Background: Postoperative ileus prolongs both hospital stay and patients’ morbidity, having at the same time a great impact on health care costs. Coffee, a worldwide popular, cheap beverage might have an important effect on the motility of the postoperative bowel. Methods: PubMed, Scopus, and Cochrane Central Register of Controlled Trials were systematically searched. Results: Four studies met the inclusion criteria of our meta-analysis. A total of 341 patients were included. The postoperative administration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 38 publications
2
38
0
3
Order By: Relevance
“…Gastrointestinal dysmotility is a common problem in the intensive care patients, compounded by opiates, surgery, sepsis and electrolyte abnormalities 53 . Caffeine has been shown to effectively improve gastrointestinal motility with no signi cant side effect 54 . Caffeine intake has been historically limited in peri-operatively in patients due to the risk of vasospasm and risk of cardiac events 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal dysmotility is a common problem in the intensive care patients, compounded by opiates, surgery, sepsis and electrolyte abnormalities 53 . Caffeine has been shown to effectively improve gastrointestinal motility with no signi cant side effect 54 . Caffeine intake has been historically limited in peri-operatively in patients due to the risk of vasospasm and risk of cardiac events 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…We have read with great interest the paper "Effect of Caffeine Intake on Postoperative Ileus: A Systematic Review and Meta-Analysis and Muscle Breakdowns" by Gkegkes et al [1], and we found his manuscript of importance with a view to clinical prevention. The paper reviewed the available evidence concerning the postoperative administration of coffee in enhanced recovery in the postoperative period.…”
Section: Dear Editormentioning
confidence: 94%
“…Gkegkes et al [1] referred that pathophysiology concerning postoperative ileus is poorly defined and dependent on a multitude of factors; the most important of which are inflammation, the effects of surgical manipulation, administration of opioids, autonomic dysfunction, and deregulation of the gastrointestinal hormone activity and electrolyte fluctuations. Caffeine acts positively on inflammation and promotes nitric oxide synthesis in the endothelium by the release of Ca2 from the endoplasmic reticulum through activation of the ryanodinesensitive Ca2 channel and the suppression of cyclic guanosine monophosphate degradation in the isolated rat aorta, resulting in the caffeine-induced augmentation of endothelium-dependent vasodilatation.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, NOM presented a success rate of 72.7% within ve years. (13) Additionally, several systematic reviews have reported clinical bene ts of NOM versus surgical approach (1,6,(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%